Evidence for the 125 GeV Higgs boson decaying to a pair of tau leptons - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (Springer Berlin Heidelberg, 2014)
A search for a standard model Higgs boson decaying into a pair of τ leptons is performed using events recorded by the CMS experiment at the LHC in 2011 and 2012. The dataset corresponds to an integrated luminosity of 4.9 fb-1 at a centre-of-mass energy of 7TeV and 19.7fb-1 at 8TeV. Each τ lepton decays hadronically or leptonically to an electron or a muon, leading to six different final states for the τ-lepton pair, all considered in this analysis. An excess of events is observed over the expected background contributions, with a local significance larger than 3 standard deviations for mH values between 115 and 130 GeV. The best fit of the observed H → ττ signal cross section times branching fraction for mH = 125 GeV is 0.78±0.27 times the standard model expectation. These observations constitute evidence for the 125 GeV Higgs boson decaying to a pair of τ leptons.